2020
DOI: 10.4067/s0717-95022020000300565
|View full text |Cite
|
Sign up to set email alerts
|

Toward the First Definition of Taste Rosea in Female Breasts: Histological Analysis

Abstract: DEMIRCI, T.; OZMEN, S.; AYDIN, N.; AYDIN, M. D.; CAGLAR, O.; AHISKALIOGLU, A.; KARADENIZ, E. ; GUNDOGDU, B. & HACIMUFTUOGLU, A. Toward the first definition of taste rosea in female breasts: Histological analysis. Int. J. Morphol., 38(3):565-569, 2020. SUMMARY:Although various neuropsychochemical theories have been established about why breastfeeding mothers feel hedonic sensation, the underlying neural mechanism has not been adequately clarified. We aimed to investigate if there is hedonic sensation-initiated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Tongue taste information conveys with facial, glossopharyngeal, vagal nerves 2 ; genital-mammarial taste bud information carry with pudendal nerves in animals. 3,4 All of those networks may be responsible for body glucose regulation. Our previous studies have shown that blood glucose regulating mechanisms should include mammarial and genital taste buds in addition to oral taste buds and pancreas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tongue taste information conveys with facial, glossopharyngeal, vagal nerves 2 ; genital-mammarial taste bud information carry with pudendal nerves in animals. 3,4 All of those networks may be responsible for body glucose regulation. Our previous studies have shown that blood glucose regulating mechanisms should include mammarial and genital taste buds in addition to oral taste buds and pancreas.…”
Section: Discussionmentioning
confidence: 99%
“…21 Our previous studies and publications proved that pleasurecreating hedonic sensations originating from taste bud including organs such as tongue, mammary gland and genitalia reach to the spinal cord and mentioned higher brain centers to regulate all body-organ glucose levels. 3,4 How the pancreas feels blood sugar, which cell group firstly informs glucose regulation requirement, and how the first information is created in the pancreas has not yet been clearly defined. According to our hypotheses, All values given mean ± standard deviation, Group I: Normal, Group II: Hyperglicemic, Group III: Hypoglicemic.…”
Section: Discussionmentioning
confidence: 99%